Disfunção cardíaca em animal nocaute para o receptor do tipo 2 para bradicinina - Danilo Roman Campos (2009)
The Kinins are important peptides concerning control of cardiovascular function. Their action mechanism depend on the activation of two distinct receptor, type 1 and 2 bradykinin receptor (B1R and B2R). They both are coupled to G protein, which are responsible to activate different intracellular pathways, involved in different cellular process. Their role in the control of heart function is not well understood. Based on this issue, we decided to evaluate the heart physiology of mouse knockout to type 2 receptor of bradykinin (B2R-/-), in order to evaluate the B2R function in the heart physiology. Using langendorff technique we observed a reduced heart function, in terms of contraction. To evaluate the mechanism involved in the heart dysfunction, we used isolated cardiomyocyte. We evaluated the cellular contraction and both, left and right ventricular cardiomyocytes presented reduction in cell shorthening. Furthermore, time to 50% to contraction and relaxation were increased. In order to investigate the electrical properties of left ventricular cardiomyocyte in B2R-/-, we used patch-clamp technique in current and voltage-clamp mode. When comparing control and B2R-/- we observed: increased time to repolarization of action potential; increased resting potential; inward potassium rectification (IK1) is not altered; transient outward potassium current (Ito) was reduced; delay potassium current (Ik) was not altered and L-type calcium current (ICa,L) was attenuated. Besides, kinetics process concerning Ito and ICa,L, in a overall mean were altered. We evaluated calcium release from sarcoplasmatic reticulum using confocal microscope and we obtained a reduction in calcium release from sarcoplasmatic reticulum from B2R-/-. To characterize alterations in the production of reactive oxygen species we evaluate basal production of superoxide in cardiomyocyte and B2R-/- presented an increased production when comparing to control. We also investigated the participation of nitric oxide (NO) in modulate Ito, ICa,L and calcium release from sarcoplasmatic reticulum. We observed that NO is, in parts, responsible to the reduction in Ito and ICa,L in cardiomyocytes of B2R-/-. However NO is not responsible to the reduction in calcium transient. Taking together, our results indicate that B2R-/- mice present a reduction in heart function attributed to alterations in electrophysiology, calcium transient and generation of reactive oxygen species. Furthermore, the dysfunction presented is, in parts, due to excessive production of NO. In sum, the heart phenotype presented by B2R-/- mice is similar to many models of heart failure, indicating that B2R-/- mice develop spontaneous heart failure.